In Developing World… Managing late blight on potato and its future risks - Forbes, G A (Indian Horticulture, 2019)
Potato late blight caused by Phytophthora infestans is one of the most important plant diseases. Estimates due to both crop loss and fungicide use go as high as 15 billion US$ per year. It is virtually ubiquitous, occurring almost everywhere potato is produced, but its intensity is variable depending principally on climatic factors. The disease is primarily managed with frequent fungicide applications, and the role of host plant resistance has been considered negligible. However, some recent analysis indicate that host resistance is playing an important role in some parts of the developing world, which gives hope for the potential of this disease management strategy. Use of host resistance to reduce risk of crop loss and modulate fungicide dependency may be particularly promising in areas where cultivar turnover is still occurring. Till date, the greatest source of risk to farmers has been greater disease pressure due to pathogen evolution towards increased aggressiveness, and/or fungicide resistance. Risk due to climate change would appear to be highly variable, with disease intensity increasing in some areas and decreasing in others. Nonetheless, in some regions increasing temperatures will move potato late blight into areas where it was previously not problematic, this may lead to important changes in production practices.